Exile and suffering : a selection of papers read at the 50th anniversary meeting of the Old Testament Society of South Africa OTWSA/OTSSA, Pretoria, August 2007 - Becking, Bob.; Human, Dirk J. (Oudtestamentische Studiën, Old Testament Studies, 2009)
At the fiftieth anniversary of the Old Testament Society of South Africa a conference was organized on the theme Exile and Suffering. This volume contains a selection of the papers presented. Focal questions are such themes as: What do we really know about the Exile? To what degree did suffering take place? How did the Ancient Israelites cope with the disaster? Where the ancinet traditions sufficient to deal with the Exile? Or did this period produce new forms of 'theology'? The significance of the Exile as a matrix for understanding suffering until this day is also dealt with.